Thermal Analysis on Kerosene Oil-Based Two Groups of Ternary Hybrid Nanoparticles (CNT-Gr-Fe3O4 and MgO-Cu-Au) Mix Flow over a Bidirectional Stretching Sheet: A Comparative Approach - Shilpa Choudhary; Ruchika Mehta; Nazek Alessa; Sanju Jangid; M. Venkateswar Reddy (Journal of Engineering)
The present work examines the impressions of radiation impact on the three-dimensional non-Newtonian MHD Casson flow of ternary hybrid nanofluids over a symmetrical stretching sheet with magnetic impression and heat generation/absorption. The unique boost in thermal efficiency and development of the rate of heat transport as valid to the dynamics of energy and coolant in automobiles is what has led to an increase in knowledge of hybrid nanofluid. For the study, two groups of ternary nanoparticles (CNT-Gr-Fe3O4 and MgO-Cu-Au) are combined with the base fluid kerosene oil. A nonlinear partial differential equation system is created while keeping in mind some reasonable presumptions. Using the similarities transformation, PDE’s are changed into nonlinear ODE’s. Also, it is then mathematically simplified with the bvp4c technique. The consequences of an exclusive group of unique impacts on motion characteristics, skin friction coefficient, thermal field impressions, heat transport rate, concentration distribution, and mass transfer rate are described clearly. The motion in the x and y directions decays with increasing the Casson fluid parameter 0.04≤β≤0.06 and magnetic impact 6≤M≤10 for ternary groups I and II. An energy upsurge profile appears for radiation impression (1 ≤ Nr ≤ 20) and heat source/sink (0.1 ≤ Q ≤ 1.5). When compared to rising Dufour number (0.1 ≤ Du ≤ 0.9) and heat source/sink values (0.1 ≤ Q ≤ 1.5), the Nusselt number decreases. The volume fraction 0.1≤ϕ≤0.3 of ternary nanoparticles rises the velocity (in both directions) and thermal distributions. Also, the Nusselt number enhances for both ternary groups when increasing thermal radiation (1 ≤ Nr ≤ 20).